Differential Roles for VviGST1, VviGST3, and VviGST4 in Proanthocyanidin and Anthocyanin Transport in Vitis vinífera - Pérez-Díaz, Ricardo; Madrid-Espinoza, José; Salinas-Cornejo, Josselyn; González-Villanueva, Enrique; Ruiz-Lara, Simón (Frontiers in Plant Science, 2016)
In plant cells, flavonoids are synthesized in the cytosol and then are transported and accumulated in the vacuole. Glutathione S-transferase-mediated transport has been proposed as a mechanism involved in flavonoid transport however whether binding of flavonoids to GST or their transport is glutathione-dependent is not well understood. Glutathione S-transferases from Vitis vinífera (VviGSTs) have been associated with the transport of anthocyanins, however their ability to transport other flavonoids such as proanthocyanidins (PAs) has not been established. Following bioinformatics approaches, we analyzed the capability of VviGST1, VviGST3, VviGST4 and Arabidopsis TT19 to bind different flavonoids. Analyses of protein-ligand interactions indicate that these GSTs can bind glutathione and monomers of anthocyanin, PAs and flavonols. A total or partial overlap of the binding sites for glutathione and flavonoids was found in VviGST1, and a similar condition was observed in VviGST3 using anthocyanin and flavonols as ligands, whereas VviGST4 and TT19 have both sites for GSH and flavonoids separated. To validate the bioinformatics predictions, functional complementation assays using the Arabidopsis tt19 mutant were performed. Overexpression of VviGST3 in tt19-1 specifically rescued the dark seed coat phenotype associated to correct PA transport, which correlated with higher binding affinity for PA precursors. VviGST4, originally characterized as an anthocyanin-related GST, complemented both the anthocyanin and PA deposition, resembling the function of TT19. By contrast, VviGST1 only partially rescued the normal seed color. Furthermore the expression pattern of these VviGSTs showed that each of these genes could be associated with the accumulation of different flavonoids in specific tissues during grapevine fruit development. These results provide new insights into GST-mediated PA transport in grapevine and suggest that VviGSTs present different specificities for flavonoid ligands. In addition, our data provide evidence to suggest that GST-mediate flavonoid transport is glutathione-dependent.